TLR7 Polymorphism (rs179008 and rs179009) in HIV-Infected Individual Naïve to ART. (20th May 2020) - Singh, HariOm; Samani, Dharmesh; Aggarwal, Sumit
Abstract : Toll-like receptors (TLRs) play an important role in the innate immune response to HIV infection. Single nucleotide polymorphism (SNP) in TLR7 (Gln11Leu) gene has been associated with a rapid decline of CD4T cell count. Hence, we assessed the TLR7 (rs179008, Gln11Leu (A/T) and rs179009, IVS2-151 (A/G)) polymorphism in 150 HIV-infected individuals naïve to ART and 158 healthy controls. The genotyping of TLR7 Gln11Leu (A/T) and IVS2-151 (A/G) polymorphisms was done using the PCR-RFLP method. In univariate analysis, none of the genotype and haplotype of TLR7 Gln11Leu (A/T) and IVS2-151 (A/G) polymorphism differed significantly between HIV-infected individuals and healthy controls. The occurrence of TLR7 rs179009AG genotype in the codominant model and rs179009 AG-GG genotype in the dominant model was significantly reduced in HIV-infected individuals as compared to healthy controls (18.0% vs. 29.1%, OR = 0.42, P = 0.016 ; 26.7% vs. 36.7%, OR = 0.52, P = 0.016 ). TLR7 rs179009AG genotype was significantly underrepresented in the intermediate HIV disease stage compared with healthy controls (OR = 0.03, P = 0.04 ). TLR7 rs179009AG genotype expressed higher in tobacco-consuming HIV-infected individuals compared with nonusers (OR = 1.71, P = 0.47 ). In conclusion, rs179009 AG-GG and AG genotypes were found reduced in HIV-infected individuals as compared to healthy controls; their higher prevalence in health individuals clearly support that they are associated with reduced risk of acquisition of HIV-1 infection.